OC-43 A family case of an adenomatous polyposis. (6th June 2017) - Ignat, Ancuta; Burlea, Marin; Paduraru, Gabriela; Caba, Lavinia; Haba, Danisia; Lupu, Vasile Valeriu
Abstract : Introduction: The inherited gastrointestinal polyposis syndromes are divided into adenomatous and hamartomatous varieties. The adenomatous polyposis syndromes include familial adenomatous polyposis coli, Gardner's syndrome and Turcot's syndrome. Gardner's syndrome is characterised by the presence of numerous intestinal polyps, with extra-intestinal manifestations of bone and soft-tissue such as desmoid fibromatosis, lipomas, osteomas and epidermal cysts. Cases report: We report the cases of 2 brothers (17-year-old girl and 15-year-old boy) with typical symptoms of Gardner's syndrome who were sent from the Genetics Clinic at the V-th Paediatrics Clinic of "St. Mary" Children's Emergency Hospital to perform a colonoscopy (for highlighting the colonic mucosa damage). Their mother and their maternal grandfather had a suggestive history of a similar disease. The patients were diagnosed to have colonic polyps. Conclusion: The patients with Gardner's syndrome must be closely followed-up, since there is a constant threat to their lives at any age.